Muscular-stage Dissection during Far Lateral Approach and Its Transcondylar Extension - Sato, Akihito; Hirai, Sakyo; Obata, Yoshiki; Maehara, Taketoshi; Aoyagi, Masaru (Journal of Neurological Surgery Part B: Skull Base, 2018)
Background The far lateral approach includes exposure of the C1 transverse process, vertebral artery, posterior arch of the atlas, and occipital condyle. We designed a method for systematic muscular-stage dissection and present our experience with this approach.Operative Methods We used a horseshoe scalp flap that was reflected downward and medially. The lateral muscle layers were separated layer to layer to expose the suboccipital triangle. The medial muscle layers were separated in the midline and reflected in a single layer. At this stage, the midline of the C1 process and the foramen magnum were identified. The rectus capitis posterior major muscle was reflected to expose the posterior arch of the atlas. The C1 transverse process and vertebral artery were identified by reflection of the superior oblique muscle. The occipital condyle was separated accordingly.Results We used this method of muscular dissection in 10 patients (foramen magnum meningioma, n = 5; hypoglossal schwannoma, n = 2; others, n = 3). Systematic muscular-stage dissection facilitates identification of the anatomical landmarks with no vertebral artery injury. Gross total removal was obtained in all 9 patients with complex tumors. The patient with vertebral artery dissection successfully underwent proximal clipping.Conclusion Our muscular-stage dissection could contribute to safe and effective surgery for the far lateral approach.
Keywords: far lateral; skull base; surgical approach; muscular dissection